Evaluasi Akuntansi Kombinasi Bisnis dengan Penerapan Standar Internasional Pelaporan Keuangan (IFRS) pada PT Garuda Indonesia (Persero) Tbk - Ayuk Septiyaningsih; Ifta Ngainun Nida; Putri Retnaningsih (Jurnal Manajemen Kreatif dan Inovasi, 2024)
The aim of this research isnto assess the implementation of Internasional Financial Reporting Standars (IFRS) at PT Garuda Indonesia Tbk, especially inte accounting aspect of business combinations. This research method is quantitative and uses analysis through a literatur study approach. The data used was obtained from the financial report of PT Garuda Indonesia Tbk for 2011, 2015, daj 2018, taken from official company sources. Research findings show that PT Garuda Indonesia Tbk has succesfully implemented the PSAK 22 business merger accounting standard (revised 2011, 2015, dan 2018) which as been adapted to IFRS with efficiency in preparing financial reports. The impact of this research is to provide a significant contribution in helping shreholders and other related partiesnij evaluating the extent to which companies comply with applicable financial reporting regulations.